Optimized design of environmentally-friendly polydopamine nanoparticles for the stabilization of both thermo- and photo-oxidation of polypropylene: Size effects. (December 2022) - Chen, Jiaxing; Xia, Lei; Kong, Miqiu; He, Yusong; Lv, Yadong; Huang, Yajiang; Li, Guangxian
Abstract: Despite the huge success of commercial stabilizers (antioxidants, UV absorbers, etc.) on the functionality enhancement and lifetime prolonging of polymers, their toxicity on the environment has been raising severe concerns. Therefore, producing environmentally benign stabilizers via green chemistry has been attracting researchers' attention. In this work, we demonstrated the potential of mussel-inspired polydopamine nanoparticles (PDA-NPs) with intrinsic biocompatibility for the enhancement of both thermo- and photo-oxidation stability of polypropylene (PP). The effects of PDA-NPs size on the antioxidative performance of PP were systematically explored. PDA-NPs with different sizes of 471 nm, 284 nm, and 98 nm were synthesized first by tuning the pH values of initial dopamine solutions. The antioxidation ability of PDA-NPs for PP increased remarkably with the decreasing size, which was attributed to a higher specific area and more available semiquinone structure of smaller PDA-NPs. Compared with pure PP, the oxidation induction time (OIT) and onset thermal decomposition temperature of optimized PP composites can be increased significantly from 9.8 min to 26.0‍‍ min by 165% with the addition of only 0.5 wt% PDA-NP (98 nm), while the thermo- and photo-oxidative degree (formation of carbonyl products) on the surface can be decreased by 53% and 92% at most, respectively. However, the dependence of UV protection ability of PDA-NPs for PP on their size is non-monotonic. As indicated by cross-sectional fluorescence and modulus imaging, the shallowest degradation depth was observed for PP composites with the PDA-NP size of 284 nm other than that of 98 nm. These results have demonstrated the feasibility of PDA-NPs as robust stabilizers and the importance of size design for optimizing the anti-aging efficiency of PDA-NPs, providing valuable insights into the development of multifunctional stabilizers for environmental sustainability. Highlights: Polydopamine nanoparticles (PDA-NPs) significantly improved both thermo- and photo-oxidation stability of polypropylene. The antioxidation ability of PDA-NPs for PP increased remarkably with the decreasing size of PDA-NPs. The dependence of UV protection ability of PDA-NPs for PP on their size is non-monotonic.